Comparative Analysis of Beet Juice and Red Guava Juice against Erythrocyte and Hematocrit Levels in Post-partum Women - Nurhasanah, Cut; Idiana, Andri; Santi, Putri; Yushida, Yushida (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Post-partum physiological bleeding can cause post-partum mothers to experience anemia; often, post-partum mothers are limited by nutrient and fluid intake to keep the body strong and have ideal body weight. AIM: The aim of the study is to knowing the difference between beet juice and Guava juice on erythrocyte and hematocrit (HTC) levels in post-partum mothers at Darul Imarah Health Center, Darul Imarah District, Aceh Besar District. METHODS: This was a quasi-experimental study with a pre-post test design using a randomized controlled trial. The population of post-partum mothers in the Darul Imarah Health Center, Darul Imarah District, Aceh Besar District. The sample selection is purposive sampling with inclusion and exclusion criteria; the sample is 45 people. RESULTS: The results showed differences in erythrocyte and HTC levels between before and after giving guava and iron (Fe) juices with a p-value of 0.00 <0.05. Beet juice increases the average erythrocytes and HTC levels higher than guava juice. There were significant differences in erythrocyte levels in the guava + Fe, beet + Fe, and control (Fe) treatment groups with a p-value of 0.001 <0.05. the difference in the average difference in erythrocyte levels between the guava and beet treatment groups was 0.03. The treatment group Bit + Fe had a higher mean erythrocyte level different than the guava + the treatment group and the control group (Fe). There was a significant difference in HTC levels in the guava + Fe, beet + Fe, and control (Fe) treatment groups with a p-value of 0.001 <0.05. the difference in the average difference in erythrocyte levels between the guava and beet treatment groups was 0.03. The treatment group Bit + Fe had a higher mean difference in HTC levels than the guava + the treatment group and the control group (Fe). CONCLUSION: There is a significant difference in erythrocytes and HTC levels between before and after giving guava juice and beet juice to post-partum mothers with a p-value of 0.00 <0.05. Beet juice increases the average level of erythrocytes and HTC, which is higher than guava juice in post-partum mothers at the Darul Imarah Health Center.